Measurements of ultrasonic velocity in the molten salt mixture CdC12-NaCl - ZAPIÓR, Bronisław; JUSZKIEWICZ, Adam; GRZEGORCZYK, Andrzej (Archives of Acoustics, 1976)
The measurement of the ultrasonic velocity was carried out for the molten salt mixture CdCl2-NaCl, in mole fraction ratios, for the temperature range 580-880°C. The adiabatic compressibility was calculated for each concentration at the temperature 680°C. The isothermal velocity and excess velocity as functions of the mole fraction have been illustrated for the temperature 840°C.